Antidiabetic Efficacy of Nigella sativa Linn. in Alloxan-induced Diabetic Rabbits - F, Ikram; F, Hussain (IIUM Medical Journal Malaysia, 2014)
Introduction: Diabetes mellitus (DM) is the most common metabolic disease worldwide. Multiple medications and side effects, the most significant and prevalent themes in diabetes mellitus ultimately determine novel directions and avenues in drug discovery. The present study was conducted to investigate antidiabetic efficacy of extracts of Nigella sativa Linn. seeds (NS). Methods: Alloxan-induced diabetic rabbits (n = 28) were divided into four groups, including diabetic control. Two groups were treated with NS methanol (NSM) and ethanol (NSE) extracts, and one group were given glibenclamide. Serum glucose, triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and very low-density lipoprotein cholesterol (VLDL-C) were measured by kit methods. Results: NS demonstrated hypoglycaemic and hypolipidaemic activities. Although NS treatments decreased blood glucose, TC, TG and LDL-C and increased HDL-C in diabetic groups, it was unable to normalize all the parameters. NS extracts did not regenerate β-cells of islet of the pancreas. Glibenclamide showed significant (P<0.05) decline in hyperglycaemia and hyperlipidaemia as well as prominent renewal of β-cells of islets of Langerhans. Few surviving beta cells of islet of the pancreas were apparent in NSM treated group. Standard drug glibenclamide showed a significant decline in hyperglycaemia and hyperlipidaemia as well as prominent renewal of beta cells. Conclusion: N. sativa L. extracts have curative effects in terms of diabetes-induced disturbances of glucose and lipids. Further investigations are suggested to ascertain the therapeutic role of NS on islet histopathology in diabetes mellitus.